Online research about online research: advantages and disadvantages - Topuzovska Latkovikj, Marija; Borota popovska, Mirjana (Foundation Pro Scientia Publica, 2020)
Aim. Many people believe that the Internet may revolutionise several disciplines byallowing easier and faster data collection, larger and geographically diverse samples, andtherefore collecting more representative data. However, others are skeptical of its usabilityas well as its practical value. The paper’s aim is to highlight both positive and negativeoutcomes in the online research.Methods. The paper is based on the e-methodological approach by using exclusivelyonline data and online research methods: secondary data/articles with an open accessabout the topic in the literature review section; and online forum as an online researchmethod for the data collection.Results. As the most common advantages are recognised: quick access to information,wide geographical scope, a larger sample size leading to greater statistical power, reducedcost of conducting empirical research, support from online search engines and data bases,open data sources, no need for face-to-face interaction, no paper wasted. The most commondisadvantages appointed by the respondents are: the need of evaluation for the accuracyof the online sources, the need for Internet access, limited access or high costs of some databases, the contrast between fresh and redundant data available, irrelevant data, the needand knowledge for precise formulation of the key phrases/questions, users’ multiple accounts,AI involvement, low motivation of the targeted respondents, unreliable answers, etc.Conclusions. It is interesting that the narratives confi rm the already highlighted positiveand negative outcomes in the online research process as they are already elaboratedin the theoretical frame. This research proves that is possible to use the online forums forgathering data, especially in the kinds of networks, where the most important attribute ofthe respondents is known solely by the membership itself. Because the internet is widespread,easily available, low costing, it is important to open a wide discussion about overcomingshortcomings on online research approach, and come to the useful and improvedsolutions.